The Carbon Holdings of Northern Ecuador's Mangrove Forests. Issue 1 (2nd January 2017) - Hamilton, Stuart E.; Lovette, John P.; Borbor-Cordova, Mercy J.; Millones, Marco
Abstract : Within a geographic information systems environment, we combine field measures of mangrove tree diameter, mangrove species distribution, and mangrove tree density with remotely sensed measures of mangrove location and mangrove canopy cover to estimate the mangrove carbon holdings of northern Ecuador. We find that the four northern estuaries of Ecuador contain approximately 7, 742, 999 t (±15.47 percent) of standing carbon. Of particularly high carbon holdings are the Rhizophora mangle –dominated mangrove stands found in and around the Cayapas-Mataje Ecological Reserve in northern Esmeraldas Province, Ecuador, and certain stands of Rhizophora mangle in and around the Isla Corazón y Fragata Wildlife Refuge in central Manabí Province, Ecuador. Our field-driven mangrove carbon estimate is higher than all but one of the comparison models evaluated. We find that basic latitudinal mangrove carbon models performed at least as well, if not better, than the more complex species-based allometric models in predicting standing carbon levels. In addition, we find that improved results occur when multiple models are combined as opposed to relying on any one single model for mangrove carbon estimates. The high level of carbon contained in these mangrove forests, combined with the future atmospheric carbon sequestration potential they offer, makes it a necessity that they are included in any future payment for ecosystem services strategy aimed at using forest systems to offset CO2 emissions and mitigate predicted CO2 -driven temperature increases.